Morbidity among mine workers: a cross sectional study in Chitradurga, Karnataka, India - Rajashekar, Somarouthu; Sharma, Prajna (International Journal Of Community Medicine And Public Health, 2017)
Background: Workers represent half the world’s population and are the major contributors to economic and social development. Their health is determined not only by workplace hazards but also by social and individual actors and access to health services. Work-related morbidity and mortality result in suffering and hardship for worker as well as to his or her family. Thus occupational health of working people are crucial prerequisites for overall socioeconomic and sustainable development. The aims and objective were to assess the health status of the people working in mines and study their occupational hazards. Methods: A cross sectional study was conducted in three actively working mines of Chitradurga city for a period of one year. Complete enumeration method was used to include 493 mine workers. Results: Sesagoa mines were the biggest among the selected mines (69.5% workers). Majority belonged to the age group of 20-30 years with 37.5%, 69% workers were field workers. Around 76.3% workers were working since 1-5 years. 45.20% and 11% workers had undergone pre placement examination and periodic examination respectively. Personal Protective Equipments (P.P.E) were used by 90.50% workers. History of allergy was seen in 21.7% workers, while 11.2% workers reported history of vector borne diseases. Trouble smelling was found in 1.8% workers while 1.6% workers had trouble hearing. Conclusions: Health education on pre placement, periodic examination and use of PPE was found to be less which on itself can be the reason for morbidities among the mine workers hence efforts must be made to improve their knowledge regarding these.